QUALITY OF NATURAL AND PULPED COFFEE AS A FUNCTION OF TEMPERATURE CHANGES DURING MECHANICAL DRYING - Oliveira, Pedro Damasceno; Biaggioni, Marco Antônio Martin; Borém, Flávio Meira; Isquierdo, Eder Pedroza; Vaz Damasceno, Mariana de Oliveira (Coffee Science - ISSN 1984-3909, 2018)
The research evaluates the sensorial quality of processed and dried coffee beans in different ways. Two types of processing were performed: dry and wet; And seven drying methods: drying in the terrier, and mechanical drying with heated air at 50ºC until coffee reaches 30% water content, followed by drying with air heated to 35ºC until reaching 11% water content; drying in fixed-layer dryers with heated air at 45 ° C until the coffee reaches 30% water content, followed by drying with heated air at 35 ° C until reaching 11% water content; and drying in fixed layer dryers with heated air at 40 ° C until coffee reaches 30% water content, followed by drying with heated air at 35 ° C until reaching 11% water content; drying in fixed layer dryers with heated air at 35 ° C until the coffee reaches 30% water content, followed by drying with heated air at 50 ° C until reaching 11% water content; drying in fixed-layer dryers with heated air at 35 ° C until the coffee reaches 30% water content, followed by drying with heated air at 45 ° C until reaching 11% water content; drying in fixed-layer dryers with heated air at 35 ° C until the coffee reaches 30% water content, followed by drying with heated air at 40 ° C until reaching 11% water content. The mechanical drying system consisted of three dryers of fixed layer, allowing the control of temperature and drying flow. The cafes were tasted according to the evaluation system proposed by the American Specialty Coffee Association (SCAA). Analyzes of the physical-chemical composition and physiological quality of the grains were carried out, involving: acidity grease, potassium leaching, electrical conductivity, color and germination. The results show that the pulped coffee is more tolerant to drying than the natural coffee, regardless of how it was dried.